Linkage-linkage disequilibrium dissection of the epigenetic quantitative trait loci (epiQTLs) underlying growth and wood properties in Populus - Lu, Wenjie (The New phytologist, 2020)
© 2019 The Authors New Phytologist © 2019 New Phytologist Trust.